The Impact of German and Soviet Politics towards the Establishment ofthe Baltic Union in 1919-1940 - Butkus, Zenonas (Lietuvos istorijos studijos, 2007)
Following the weakening of Russia and Germany, modern Baltic states – Lithuania, Latvia and Estonia – were established during World War I. Even though they succeeded in liberating themselves from the foreign yoke, the newly created states found it impossible to break free from the political and diplomatic influence exerted by the said great states. Postwar democratic development, outburst of democracy in international relations, the foreign policy conducted by England and France in North-Eastern part of Europe, as well as the activities of the Nations Union could lessen this influence only to a certain extent. The process of breaking totally free from this influence was also hindered by the failure of the Baltic countries to unite, join their efforts and thus stabilize the position of the region on the international political scene.The unification and cohesion of the region was also impeded by USSR and Germany, which implemented a conscious and well planned policy, deliberated on the top hierarchy level. It was conceived as a precondition towards the revisionism about to be introduced. In the attempt to undermine the unity of the Baltic states and hinder the establishment of the Union, both big states applied an extremely wide range of measures. Within this context, the following five measures, most widely applicable to implement the strategy, will be identified and dealt with:The first measure: Direct threats, mostly practiced by the Soviets. Latvia and Estonia were instructed that in the case of establishing the Union confrontation policy would be introduced, with the Soviet troops deployed near their borders. Lithuania was threatened with an immediate termination of any support related to the Vilnius problem.The second measure: Measures of economic pressure were applied, luring the Baltic countries with the benefit related to the income from Soviet transit and rules of export restrictions to Germany.The third measure: Attempts were undertaken to discredit the most active supporters of the Baltic union, to oust them from power and force them to resign.The fourth measure: Attempts were made to cause tension and discord among the Baltic countries; disagreements on various matters were instigated, in particular focusing on the conflict between Lithuania and Poland. Preconceived notion was imposed in Lithuania that its union with Latvia and Estonia would result in reconciliation with Poland, which would not return Vilnius afterwards. Germany tried to exert its influence in Latvia and Estonia, shaping an opinion that ostensibly they should not join forces with Lithuania, which governed the „German“ Klaipėda. After all, Lithuania was known to be a backward country, devoid of any civilization. Furthermore, attempts were made to instill enmity among the politicians of the Baltic countries, by working on their personal ambitions.The fifth measure: The USSR and German politicians and diplomats preferred to penetrate into the „natural“ political process of the Baltic countries rather than plot artificial intrigues. They supported the political forces which opposed the establishment of the Union or were in favour of such a version of the Union which had no potential future. Attempts were made to instill animosity among supporters of different versions of the Union; apart from the prevailing discord and disagreements, additional measures were taken to promote hardliner tactics. Furthermore, it was attempted to instill hostility among different institutions involved in foreign policy.The measures hindering progress in the Baltic states were well matched to the particularities of the political process in every country in question. The pursuit to curb the establishment of the Baltic Union was characterised by the collaboration between the USSR and Germany, resulting in a greater efficiency of the measure applied.More pronounced interferences into the consolidation of the Baltic countries are traced back to the mid 20-ies, reaching the peak in 1925, when both big states completed the elaboration of special programs of such interferences. The intense unification process was discontinued that year, to be renewed only in 1934, when the Baltic Antante was established. It was in Lithuania’s interests then to draw closer to Latvia and Estonia – after Poland and Germany had signed nonaggression pact, Lithuania’s international situation worsened. The Soviets no longer hindered the establishment of the Baltic Antante – they were hoping to use Lithuania as a platform to exert influence upon all three Baltic countries, as well as include them into the „Eastern pact“ project.The Baltic Antante succeeded in neutralizing the impact of the USSR and Germany towards the foreign policy of its members, at least to a certain extent. Latvia and Estonia, united in the same organization with Lithuania, undermined the latter’s position, which was quite favourable to the Soviets. Furthermore, Estonia’s friendly predisposition towards the policies conducted by Nazi Germany was curbed. The establishment of the Baltic Antante was predetermined by the changes on the international arena; its activities were also terminated by an external factor, namely, by the occupation of Lithuania, Latvia and Estonia.
Keywords: -